Systematic Literatur Review: Pengaruh Karakteristik Komite Audit terhadap Kecurangan Pelaporan Keuangan - Denov Irnadianis Ifada; Tsalitsa Fatiimatuzzahra; Dr. Dien Noviany Rahmatika, S.E.,M.M.,Akt.,CA (Universitas Dharmawangsa, 2024)
Characteristics of audit committees Based on data from a number of companies, we identified several characteristics of audit committees that influence the level of fraudulent financial reporting. This writing aims to prove whether there is an influence of audit characteristics on fraudulent financial statements. The systematic literature review (SLR) method with the application of this method can be carried out to review and identify journals systematically, each process uses approved procedures. In this research, the data used includes articles, journals and other relevant documents. Synonym Search data can be analyzed or evaluated using the Publish or Perish (PoP) application which accesses the Crosscref database, a semantic schoolar. At the beginning the search was limited to 154 journals. Then a review and re-analysis of the remaining 80 journals can be carried out and the inclusion and exclusion criteria can be carried out, so that the results are 47 journals in accordance with the provisions. The research results show that they can be compared to experimental results or research findings. that there are audit committee characteristics that can have a negative influence in the context of financial statement fraud.